Fuzzy-PID controller for semi-active vibration control using magnetorheological fluid damper - Kasemi, Banna; Abdul Muthalif, Asan Gani; Muhammad , Mahbubur Rashid; Fathimah, Sharmila (Elsevier, 2012)

(untitled)
Magnetorheological (MR) dampers are considered as excellent prospect to the vibration control in automotive engineering. To overcome the effect from road disturbances many control algorithms have been developed and opted to control the vibration of the car. In this study, the methodology adopted to get a control structure is based on the experimental results. Experiments have been conducted to establish the behaviour of the MR damper. In this paper, the behavior of MR damper is studied and used in implementing vibration control. The force-displacement and force-velocity response with varying current has been established for the MR damper. The force for the upward motion and downward motion of damper piston is found increasing with current and velocity. In the cycle mode which is the combination of upward and downward motion of the piston, the force having hysteresis behaviour is found increasing with current. Results of this study may serve to aid in the modelling of MR damper for control applications.